Strengthening the Islamic Economy Halal Value Chain: Sharia Diversification Strategy in an Uncertain Global Market Era - Nila Nafisatul Bashiroh; M. Nashrullah; Ahmad Ibnul Karim; Omor Faruk (Solo International Collaboration and Publication of Social Sciences and Humanities, 2026)
Objective: This study aims to analyze the role of Halal Value Chain (HVC) as a sharia diversification strategy in strengthening Indonesia's Islamic economic resilience amid global market uncertainty. Theoretical Framework: This research refers to economic theories related to sharia economics, sustainable development, and value chain analysis. This study examines how the integration of Halal sectors, such as food and beverages, Muslim fashion, halal tourism, and Islamic finance, can be a strategy for economic diversification and economic resilience. Literature Review: A literature review shows the vulnerability of conventional economic systems in the face of global geopolitical conflicts, climate change, and supply chain disruptions. This shows that an Islamic economy with the principles of justice, sustainability, and balance offers a relevant alternative. Previous research has identified the potential of HVC in promoting economic stability and inclusivity in Muslim-majority countries. Methods: This study uses a qualitative approach with a literature study method, which analyzes secondary data from scientific journals, official reports, and publications related to the halal economy in Indonesia. The data is analyzed to understand the application and impact of HVC on Indonesia's economic resilience. Results: This study shows that the implementation of HVC can be the main pillar in the diversification of the sharia economy. By integrating the halal sector, HVC contributes to the creation of new jobs, strengthens national economic resilience, and makes Indonesia the center of the global halal industry. These findings show that HVC can expand the Islamic economic base and support the growth of halal MSMEs. Implications: Strengthening HVC is essential to realize an inclusive, equitable, and sustainable Islamic economic system. This research provides insights for policymakers to strengthen the halal economy, which in turn can strengthen national economic resilience, create more jobs, and increase global competitiveness. Novelty: This research is one of the first to examine the strategic role of Halal Value Chain in the context of Indonesia's economic resilience, as well as provide a new perspective on the integration of Islamic economic principles with global market dynamics.